Higher Entrepreneurship Education: Guidelines for the Formation and Mitigation of Restrictions - Yu. B. Rubin; D. P. Mozhzhukhin (Высшее образование в России, 2022)
The publication focuses on the guidelines for the formation of entrepreneurship education as an important direction in the space of Russian higher education. Based on the functional map of entrepreneurship as a special type of professional activity and the allocation of groups of professional entrepreneurial functions, the article substantiates the appropriateness of including professional entrepreneurship competencies in educational programs on entrepreneurship. The formation of entrepreneurship competencies in graduates is regarded as achieving key learning outcomes based on the application of competency-based and practice-oriented approaches. In this conceptual context, the prospects for the implementation of the «Startup as a Diploma» program are considered.It is noted that in the absence of agreement on the recognition of entrepreneurship as an independent direction of higher education in the Russian Federation, universities are forced to search for non-standard ways to build entrepreneurship education programs aimed at the formation of necessary competencies by graduates. The authors draw attention to the possibility for graduates to obtain professional qualifications simultaneously in two types of professional activity as a result of mastering educational programs on entrepreneurship in universities, which traditionally have an industry orientation.The current results of the activities of the Federal Innovative Educational Platform created for the development of models of continuous entrepreneurship education have shown inexpediency of compulsory inclusion of entrepreneurship programs in bachelor’s and master’s degrees in management. The article supports the idea of separating entrepreneurship education as an independent direction of higher education in Russia and provides the corresponding arguments.